The miraculous journey of Edward Tulane - DiCamillo, Kate.; Ibatoulline, Bagram (Cambridge, Mass. : Candlewick Press, 2006)
Edward Tulane, a cold-hearted and proud toy rabbit, loves only himself until he is separated from the little girl who adores him and travels across the country, acquiring new owners and listening to their hopes, dreams, and histories.
Keywords: Toys -- Fiction; Rabbits -- Fiction; Love -- Fiction; Listening -- Fiction; Adventure and adventurers -- Fiction